Medication adherence: the critical step towards better patient outcome - Desai, Anish; Mahajan, Nilesh; Sewlikar, Sandeep; Pillai, Reshmi (International Journal of Basic & Clinical Pharmacology, 2017)
Medication adherence is defined as patient’s adherence to take their medications as prescribed and continue to take the prescribed medication for stipulated time frame. Medication non-adherence is a growing concern to physicians, healthcare systems, and other stakeholders (e.g., payers) and there is an increasing evidence of its prevalence and is associated with adverse clinical outcomes eventually resulting into higher costs of care. The cost of non-adherence has been estimated at 100 billion to 300 billion annually, including costs from avoidable hospitalizations, nursing home admissions, and premature deaths. Improving adherence to medication is critical to improve the quality of health care, to encourage better chronic care management, and promote better health outcomes. Reasons for non-adherence are multiple and complex. Studies have reported that poor adherence to drug dosage is due to patient perception that the disease is non-significant, adverse drug effects, lack of treatment effectiveness, and the patient’s poor or incomplete knowledge of the disease and (cost). A multifactorial approach is required to tackle this complex problem as a single approach will be ineffective for all patients. The most effective intervention is to use a combination of approaches and address literacy, behavior, and organizational issues. There are challenges as well as opportunities in addressing the public health issue of medication adherence. Changing healthcare reforms, advances in digital health media, social media and modern technologies can now provide alternatives to tackle this issue.